2022
DOI: 10.1155/2022/7680657
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related lncRNAs for Predicting Prognosis and Immune Landscape Characteristics of Uveal Melanoma

Abstract: Immune-related genes and long noncoding RNAs (lncRNAs) have a significant impact on the prognostic value and immunotherapeutic response of uveal melanoma (UM). Therefore, we tried to develop a prognostic model on the basis of irlncRNAs for predicting prognosis and response on immunotherapy of UM patients. We identified 1,664 immune-related genes and 2,216 immune-related lncRNAs (irlncRNAs) and structured a prognostic model with 3 prognostic irlncRNAs by co-expression analysis, univariable Cox, LASSO, and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As some Frontiers in Genetics frontiersin.org research showed, NSUN2-mediated RNA m5C alteration regulates the migration and proliferation of UM cells (Su et al, 2021). As Jiehua Deng et al identified, m7G may be able to control both CD8 + T cells and regulatory T cells (Treg cells), and they also suggest a connection between m7G and the prognosis of melanoma (Chen et al, 2022;Deng et al, 2022). Exploration of m7G-related lncRNA prognostic signature for predicting the immunological state in melanoma was demonstrated by Rong et al (2022).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As some Frontiers in Genetics frontiersin.org research showed, NSUN2-mediated RNA m5C alteration regulates the migration and proliferation of UM cells (Su et al, 2021). As Jiehua Deng et al identified, m7G may be able to control both CD8 + T cells and regulatory T cells (Treg cells), and they also suggest a connection between m7G and the prognosis of melanoma (Chen et al, 2022;Deng et al, 2022). Exploration of m7G-related lncRNA prognostic signature for predicting the immunological state in melanoma was demonstrated by Rong et al (2022).…”
Section: Discussionmentioning
confidence: 96%
“…As was already indicated, the signatures currently being utilized to explore the prognosis of UM patients are inadequate and not sufficiently Frontiers in Genetics frontiersin.org 09 rich. When clinical results and MRGs in UM and the tumor microenvironment were investigated, it was discovered that the TME is very important in UM (Chen et al, 2022). Researchers used MRGs to analyze immune response signatures and make prognostic predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Included in a prognostic signature; high levels associated with low survival rates [270] AC104117.3 Downregulated in high-risk tumors [271] AC104129.1…”
Section: Lncrnas Regulate Epigenetic Mechanisms In Ummentioning
confidence: 99%
“…Included in a prognostic signature; high levels associated with low survival rates [269] Upregulated in high-risk tumors [271] BACE1-AS Low levels associated with low survival rates [276] BOLA3-AS1…”
Section: Lncrnas Regulate Epigenetic Mechanisms In Ummentioning
confidence: 99%
See 1 more Smart Citation